2013
DOI: 10.1007/s00381-013-2020-0
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal outcome of isolated, nonprogressive, mild borderline fetal ventriculomegaly

Abstract: Prenatal counseling for isolated, nonprogressive, mild BVM should be mainly reassurance since it is not associated with severe neurodevelopmental delay. However, parents should be educated about the developmental milestone of children to observe and detect mild neurodevelopmental delay which can be associated with mild BVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
5
16
0
Order By: Relevance
“…Diagnoses were ASD, epilepsy and impaired psychomotor development. Thus, none of them was found to have intellectual disability or cerebral palsy, which is in line with recent studies suggesting that there is no association between severe neurodevelopmental disorders and confirmed IMV. Moreover, the prevalence of overall adverse neurodevelopmental outcome was comparable with that in the review of Pagani et al ,.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Diagnoses were ASD, epilepsy and impaired psychomotor development. Thus, none of them was found to have intellectual disability or cerebral palsy, which is in line with recent studies suggesting that there is no association between severe neurodevelopmental disorders and confirmed IMV. Moreover, the prevalence of overall adverse neurodevelopmental outcome was comparable with that in the review of Pagani et al ,.…”
Section: Discussionsupporting
confidence: 88%
“…It is reported that about 7.4–12.8% of fetuses diagnosed ultrasonographically with IMV are found postnatally to have an associated abnormality. Among these, CNS malformations are the most common structural findings, and fetal MRI has recently gained wide acceptance for the prenatal examination of fetuses with IMV. Salomon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rosenthal's fail safe-N was 278, indicating that nearly 300 articles with a mean event rate of 1% would be needed in order to make the findings trivial. Cumulative meta-analysis was performed in order to assess the role Prevalence of new (previously undiagnosed) findings on postnatal imaging (%) Pilu (1999) 17 Mercier (2001) 18 Graham (2001) 19 Greco (2001) 20 Signorelli (2004) 21 Breeze (2005) 22 Ouahba (2006) 25 Falip (2007) 13 Achiron (1993) 14 Patel (1994) 15 Vergani (1998) 3 den Hollander (1998) 16 Pilu (1999) 17 Mercier (2001) 18 Greco (2001) 20 Graham (2001) 19 Signorelli (2004) 21 Breeze (2005) 22 Goldstein (2005) 23 Gaglioti (2005) 24 Ouahba (2006) 25 Falip (2007) 26 Melchiorre (2009) 6 Weichert (2010) 28 Beegley (2010) 29 Gómez-Arriaga (2012) 30 Kutuk (2013) 31 Total Figure 6 Forest plot (random-effects model) of the reported rates of neurodevelopmental delay in cases of truly isolated ventriculomegaly, individually for each of the 20 studies included in this review and pooled for all studies. The total prevalence was 7.9% (95% CI, 4.7-11.1%).…”
Section: Resultsmentioning
confidence: 99%
“…However, Kutuk et al (12) reported that 9 out of 25 cases with mild VM showed mental or locomotor activity retardation, and some studies have supported these findings (11,(27)(28)(29). In our study, 3 cases in the "Mild VM" group and 1 case in the "Moderate VM" group had poor neurodevelopmental prognoses, which suggests that although fetuses with "Mild VM" may have more favorable outcomes than fetuses with severe ventriculomegaly, they still faced the possibility of developing an abnormality after delivery; thus, ultrasound scans and other examinations are still essential during pregnancy and after birth.…”
Section: Discussionmentioning
confidence: 98%